Research progress on physiological and biochemical characteristics of Bifidobacterium and its regulation of intestinal flora and lipid metabolism in rats - LEI Yan; CAO Xiafei; HUANG Zhishen; LIN Xiumin; CHEN Kai; XIAO Jian (Zhongguo shipin weisheng zazhi, 2023)
Intestinal microecology is the most complex and dominant microecological system in human and animals. Bifidobacterium is a probiotic that exists in the intestinal microecology and presents potential applications in several disease areas， such as prevention and control of obesity and metabolic syndrome. It has become a hot spot of research in many fields， such as food supplements and health food. Bifidobacterium can regulate rat Gut microbiota and protect intestinal mucosal barrier by regulating diet structure and energy intake， Gut microbiota microenvironment， microorganism gut brain axis and intestinal immunity， it can also regulate lipid metabolism through carbohydrate utilization pathway， anti inflammatory stress pathway， regulation of fat decomposition pathway， gene pathway， Bile acid salt coprecipitation and bacteria assimilation cholesterol pathway， and there is a two-way regulation between Gut microbiota and lipid metabolism. However， the effect of Bifidobacterium on intestinal flora and lipid metabolism varies depending on the application area， formulation and addition quantity. More in-depth control studies and clinical validation still need to establish the formulation and addition quantity. When it is applied to the food field， it may lead to the transfer of intestinal drug resistance genes or the spread of drug resistant pathogens through the way of exchanging Genetic material with the host's own Gut microbiota. In this paper， the multiple pathways and mechanisms of Bifidobacterium regulates Gut microbiota and lipid metabolism in rats were reviewed， and the related issues were prospected， in order to provide ideas for research in Bifidobacterium regulates fields.